Paracrine signals from liver sinusoidal endothelium regulate hepatitis C virus replication. Issue 2 (18th December 2013) - Rowe, Ian A.; Galsinh, Sukhdeep K.; Wilson, Garrick K.; Parker, Richard; Durant, Sarah; Lazar, Catalin; Branza‐Nichita, Norica; Bicknell, Roy; Adams, David H.; Balfe, Peter; McKeating, Jane A.
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) is a major cause of global morbidity, causing chronic liver injury that can progress to cirrhosis and hepatocellular carcinoma. The liver is a large and complex organ containing multiple cell types, including hepatocytes, sinusoidal endothelial cells (LSEC), Kupffer cells, and biliary epithelial cells. Hepatocytes are the major reservoir supporting HCV replication; however, the role of nonparenchymal cells in the viral lifecycle remains largely unexplored. LSEC secrete factors that promote HCV infection and transcript analysis identified bone morphogenetic protein 4 (BMP4) as a candidate endothelial‐expressed proviral molecule. Recombinant BMP4 increased HCV replication and neutralization of BMP4 abrogated the proviral activity of LSEC‐conditioned media. Importantly, BMP4 expression was negatively regulated by vascular endothelial growth factor A (VEGF‐A) by way of a VEGF receptor‐2 (VEGFR‐2) primed activation of p38 MAPK. Consistent with our in vitro observations, we demonstrate that in normal liver VEGFR‐2 is activated and BMP4 expression is suppressed. In contrast, in chronic liver disease including HCV infection where there is marked endothelial cell proliferation, we observed reduced endothelial cell VEGFR‐2 activation and a concomitant increase in BMP4 expression. Conclusion: These studies identify a role for LSEC and BMP4 in HCV infection and highlight BMP4 as a new therapeutic target for treating individuals with liver disease. (Hepatology 2014;59:375–384)